Susceptibilidade de isolados de Malassezia pachydermatis sensíveis e resistentes ao fluconazol frente a antifúngicos e óleos essenciais. - Jesus, Francielli Pantella Kunz de (2011)
Malassezia pachydermatis is an opportunistic fungus associated to dermatomycoses and otopathies in domestic and wild animals. The aim of this study was to compare the susceptibility profile of clinical isolates of M. pachydermatis against topic and systemic antifungals, through two standardized CLSI techniques: broth microdilution (M27-A3, 2008) and disk diffusion (M44-A, 2004). A standard Candida albicans strain (ATCC 28367) was used as quality control. M. pachydermatis isolates assayed through the broth microdilution method showed susceptibility to anfotericina-B (100%), fluconazole (97,83%), ketoconazole (95.66%), itraconazole (93,48%), followed by clotrimazole and miconazole (86.96%). The disk diffusion method showed susceptibility of 97,83% to nystatin, 95,66% to itraconazole and to amphotericin B, 91,32% to ketoconazole, 89,14% to fluconazole and of 86.96% to miconazole and clotrimazole. Through the in vitro induction of resistance to fluconazole (100%), cross-resistance was observed through the broth microdilution method among the 30 M. pachydermatis isolates against the azoles itraconazole (93%), ketoconazole (97%) and voriconazole (100%). The study of the activities of the essential oils obtained through the broth microdilution, based on geometric means of the minimum fungicidal concentration, showed that concentrations above 195.42 μg/mL, 332.49 μg/mL and 448.8 μg/mL of oregano, Mexican oregano and cinnamon essential oils, respectively, have fungicidal action against M. pachydermatis, independently of the sensitivity or resistance to fluconazole. The fungicidal activity of the essential oils against fluconazole-resistant M. pachydermatis strains is important for further therapeutic studies of this mycosis. Despite the susceptibility observed among sensitive M. pachydermatis strains suggesting fluconazole as a safe drug for the treatment of most cases of superficial and invasive malasseziosis, it is essential continuous surveillance studies to detect changes in the microbiological profile due to therapeutic practices.